Emergency medicine registrars' attitudes towards youth violence prevention interventions in Cape Town emergency centres - De Man, Martin (Division of Emergency Medicine, 2017)
Background: The City of Cape Town, South Africa, has a large youth violence problem with the highest percentage of non-natural deaths per age group in Cape Town occurring between 15 and 24 years of age. Many authorities suggest that youth violence is preventable and there is a fast growing international knowledge base on how emergency centres (ECs) and EC personnel can contribute to youth violence prevention (YVP). In order to utilise this opportunity most effectively, it is important to understand the challenges faced by EC staff, their perceptions of youth violence, and their willingness to engage in YVP interventions in the EC. There is currently no known EC-based YVP intervention in South Africa. Objectives: This study explored the perceptions and attitudes of Cape Town emergency medicine doctors on youth violence, their role in YVP and how it applies to their practice in the EC. Methods: Semi-structured focus groups, each with 3-5 Cape Town emergency medicine (EM) registrars, were conducted, using five basis questions for discussion to elicit participants' perceptions of and attitudes towards YVP. Data saturation was reached after three focus groups. Thematic analysis as described by Braun and Clarke was carried out on the focus group data sets. Results: The three focus groups were all diverse in terms of race, gender, and level of training. In terms of the "Extent of the problem" themes around acceptability and increased burden were explored."Youth Violence Prevention in the EC" focused on the need for a champion, role of the emergency doctor vs. other stakeholders and sustainability issues. Conclusions: EM registrars in Cape Town have a very limited knowledge of YVP in general and specific to the EC. They are faced with immense challenges that relate to patient load, violence directed to EC personnel, and a sense of despair or despondence in terms of ability to effect change. Concerns about the possible implementation of YVP interventions were sustained funding and sustainability in general. These and other factors influenced attitudes towards EC initiated YVP. Notwithstanding challenges, this study has shown an overwhelmingly positive attitude of EM registrars towards the concept of YVP intervention in the EC, and them being the champion or co-champion of it. Recommendations: It is recommended that EM registrars in their training time should receive theoretical and practical training on YVP which can lead to increased awareness of YVP issue, the need to know resources in the community, and in the future will make it easier to implement a pilot intervention project in a selected EC. Further research is needed on a relevant screening tool to identify high risk patients in local ECs.